Pembelajaran Calistung bagi Anak Usia Dini - Nina Rahayu (Aṭfāluna: Journal of Islamic Early Childhood Education, 2018)
Early childhood is the age when it grows its era of sensitive to the development of cognitive ability, physical-motor, language, socio-emotional, moral value of religion. At this time the administration of the lack must be adjusted to the age level. Calistung can already be applied to improve early childhood as long as the development aspect. Calistung was introduced by Maria Montessori and Gleen Doman. The process of learning education in early childhood should be recorded in order to provide meaningful concept through real experience.